Teknik Identifikasi Cepat Qira’at ‘Asyr (Analisis Infiradat al-Qurra’ atau Keunikan Bacaan Imam dan Rawi) - Khoirul Muhtadin; Mohammad Iqbal Muadzin; Suhairi (Jurnal test, 2024)
Qira'at or accepted readings of the Qur'an come from ten imams, of these ten there are twenty riwayat. The seven qira'ats were based on initiation from Ibn Mujahid, while the three following qira'ats were based on Ibn Jazari's research and decisions. Studying these twenty riwayat sequentially or all at once is considered difficult or will take a long time and is inefficient with the learning system in Indonesia, so it is not uncommon for qira'at students to choose to withdraw from studying this knowledge. Not to mention, there is a doctrine that requires you to memorize the Quran with mutqin or strength first before getting to know the science of qira'at. The author feels that fast techniques are needed to identify the readings of imams and rawi’s. With this technique, it can be seen which riwayat readings were seen and heard by the learner. This qualitative article collects unique readings or infiradat from qira'at rawi’s based on the works of Sheikh Ibrahim Dhamrah. It is hoped that this article will be easy for readers to understand because it uses the theory and approach of musykilat and gharib in reading the Quran which is already popularly known by the muslim community in Indonesia.